The continental slope current system between Cape Verde and the Canary Islands - Jesús Peña-Izquierdo; Josep L. Pelegrí; Maria V. Pastor; Paola Castellanos; Mikhail Emelianov; Marc Gasser; Joaquín Salvador; Evarist Vázquez-Domínguez (Scientia Marina, 2012)
We use hydrographic, velocity and drifter data from a cruise carried out in November 2008 to describe the continental slope current system in the upper thermocline (down to 600 m) between Cape Verde and the Canary Islands. The major feature in the region is the Cape Verde Frontal Zone (CVFZ), separating waters from tropical (southern) and subtropical (northern) origin. The CVFZ is found to intersect the slope north of Cape Blanc, between 22°N and 23°N, but we find that southern waters are predominant over the slope as far north as 24°N. South of Cape Blanc (21.25°N) the Poleward Undercurrent (PUC) is a prominent northward jet (50 km wide), reaching down to 300 m and indistinguishable from the surface Mauritanian Current. North of Cape Blanc the upwelling front is found far offshore, opening a near-slope northward path to the PUC. Nevertheless, the northward PUC transport decreases from 2.8 Sv at 18°N to 1.7 Sv at 24°N, with about 1 Sv recirculating ofshore just south of Cape Blanc, in agreement with the trajectory of subsurface drifters. South of the CVFZ there is an abrupt thermohaline transition at σϴ=26.85 kg m–3, which indicates the lower limit of the relatively pure (low salt and high oxygen content) South Atlantic Central Water (SACW) variety that coexists with the dominant locally-diluted (salinity increases through mixing with North Atlantic Central Water but oxygen diminishes because of enhanced remineralization) Cape Verde (SACWcv) variety. At 16°N about 70% of the PUC transport corresponds to the SACW variety but but this is transformed into 40% SACWcv at 24°N. However, between Cape Verde and Cape Blanc and in the 26.85 < σϴ < 27.1 layer, we measure up to 0.8 Sv of SACWcv being transported south. The results strongly endorse the idea that the slope current system plays a major role in tropical-subtropical water-mass exchange.